(untitled) (Mustansiria Dental Journal, 2018)
Aim: Film digitization is generally used to prevent potential damage or loss of original films. The method of film processing has been changing from wet to dry processing due to recent trends toward digitization of medical imaging. Materials & Methods: 50 Lateral cephalometric radiograms were used in this study. All radiographs were viewed under standardized conditions& traced. Eleven landmarks were selected to calculate 12 variables (9 angles&3 linear measurements). These traced radiographs were photographed when digitized using scan jet scanner & the same variables were measured using Dimaxis pro classic imaging software. Results: There were no statistically significant differences between traditional &digitized Linear & angular measurements except for upper incisor-Frankfort plane angle & upper incisor-lower incisor angle. Conclusion: Angular & linear measurements in digital images were comparable with that of original radiograph & are clinically acceptable. This will substantiate the benefits of digitized cephalometry in term of reliability of cephalometric analysis.